2021
DOI: 10.3390/buildings11080369
|View full text |Cite
|
Sign up to set email alerts
|

Modernist Projects of Community-Based Urban Farms in Residential Areas—A Review of Agrarian Cooperatives in the Context of Contemporary Urban Development

Abstract: This paper concerns the issue of food systems in the context of urban development. It describes relevant residential area ideas that integrate cities with food production, such as agrarian cooperatives. In the first section, modernist projects of residential areas linked with urban farms are reviewed, considering cooperative movement and the Industrial Revolution. This review shows that the aim of these historical projects was self-sufficiency and sustainability, based on local food production and broad areas … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
6
0
1

Year Published

2022
2022
2023
2023

Publication Types

Select...
6

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 52 publications
0
6
0
1
Order By: Relevance
“…Nielsen [43] found that parks are important biodiversity hotspots in urban environments [44]. Community gardens and urban agriculture are important from a biodiversity perspective [45,46]. However, urban greenery can also be a source of biogenic pollutants such as pollen and volatile organic compounds that can reduce air quality [47].…”
Section: Reasons For Measuring the Quality Of Housing And Neighbourhoodsmentioning
confidence: 99%
“…Nielsen [43] found that parks are important biodiversity hotspots in urban environments [44]. Community gardens and urban agriculture are important from a biodiversity perspective [45,46]. However, urban greenery can also be a source of biogenic pollutants such as pollen and volatile organic compounds that can reduce air quality [47].…”
Section: Reasons For Measuring the Quality Of Housing And Neighbourhoodsmentioning
confidence: 99%
“…Aktualnie w Polsce, a w szczególności w dużych miastach, przeżywamy okres zwiększonego popytu na mieszkania. Ważne jest, aby w tym okresie zadbać również o jakość realizowanych środowisk mieszkaniowych, uwzględniający zrównoważony rozwój (Nowysz, 2021;Schneider-Skalska, 2004). Budowane inwestycje powinny służyć na długie lata, ponieważ będą z nich korzystać również przyszłe pokolenia.…”
Section: Wadliwe śRodowiska Mieszkanioweunclassified
“…Today in Poland, especially in large cities, there is an increasing demand for housing. Likewise, it is also important to pay attention to the quality of real estate, which includes sustainable development (Nowysz, 2021;Schneider-Skalska, 2004). Built investments should last for many years, as they will be used by the future generations.…”
Section: Defective Housing Environmentsmentioning
confidence: 99%
“…Degradation refers to the deterioration of urban infrastructure, as well as negative phenomena occurring in the social sphere. Revitalization should contribute to improving the quality of life of residents, restoring spatial order, economic revival, and restoring social ties at different levels of urban planning [18,24,25].…”
Section: Introductionmentioning
confidence: 99%